Study to assess electricity generation in a thermal power plant using fault tree analysis model - Nygymanova A.; Ongar B.; Sarsenbayev Y. (Karaganda National Research University named after аcademician Ye.A. Buketov, 2026)
This paper presents the application of Fault Tree Analysis model for availability assessment of thermal power plant. Reliability analysis as well as availability evaluation is performed for performance evaluation of thermal power plant. Equipment maintenance data is collected from maintenance history for which the goodness of fit test viz Kolmogorov-Smirnov is conducted and parameters for the best distribution are determined. Further, reliability of subsystems at various time intervals is calculated. The Fault Tree Analysis models were developed for performance evaluation of thermal power plant. These models are employed for the subsystems of plant and furthermore availability indices are evaluated. The overall availability of 87.77% is evaluated using Fault Tree Analysis model. The comparative results are obtained from the study, which revealed that the Fault Tree Analysis model provides an availability index of the system closer to real-time data.
Keywords: reliability analysis; availability analysis; thermal power plant; Fault Tree Analysis